2021
DOI: 10.1021/acsami.1c09607
|View full text |Cite
|
Sign up to set email alerts
|

In Situ-Formed Novel Elastic Network Binder for a Silicon Anode in Lithium-Ion Batteries

Abstract: High energy density lithium-ion batteries with preferable cycling stability are critical for the development of all-electric vehicles. Silicon (Si) has demonstrated a remarkable potential for application as anode materials due to its superior capacity performance and worldwide abundance. However, Si intrinsically undergoes substantial volume fluctuation during repeated lithiation/delithiation processes, which pulverizes the Si particles and undermines the integrity of the electrode structures, thus resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…(C) Synthetic scheme of the cross-linking of PAA with isocyanate-terminated polyurethane oligomers. Adapted from ref . Copyright 2021 American Chemical Society.…”
Section: Establishing Mechanically Robust Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…(C) Synthetic scheme of the cross-linking of PAA with isocyanate-terminated polyurethane oligomers. Adapted from ref . Copyright 2021 American Chemical Society.…”
Section: Establishing Mechanically Robust Electrodesmentioning
confidence: 99%
“…Despite the strong binding effect exhibited by covalent bonds, it should be noted that cross-linking could lower the solubility of binders in solvents (e.g., H 2 O, NMP) and eventually result in inhomogeneity of the electrodes. To circumvent this issue, Liu et al reported a polymer binder with a highly stretchable and elastic network structure that was realized by in situ cross-linking of PAA with isocyanate-terminated polyurethane oligomers consisting of poly­(ethylene glycol) (PEG) chains and UPy moieties through the reaction between isocyanate and carboxyl groups during the electrode preparation process (Figure C) . This binder not only sufficiently accommodates the volume change of Si but also provides strong mechanical support to effectively sustain the integrity of the Si anodes.…”
Section: Establishing Mechanically Robust Electrodesmentioning
confidence: 99%
“…Liu and his colleagues 85 constructed a highly stretchable and elastic network polymer binder (named CPAU) for Si anodes that could be formed in situ during electrode fabrication. Figure 7c is a schematic diagram of the elastic network structure of monomer PAA and polyurethane oligomers (PUOs).…”
Section: ■ Structural Design Schemementioning
confidence: 99%
“…Copyright 2021 American Chemical Society. Panels c–e are reprinted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Structural Design Schemementioning
confidence: 99%
“…In addition, tuning the electrochemistry at the Si electrode interface, especially the formation and growth of solid electrolyte interphase (SEI), is also a critical research topic for Si-based LIBs [21][22][23][24]. Sophisticated nanostructures and binder systems have been developed to serve these purposes and thus to improve the performance of Si anodes [25][26][27][28][29][30][31]. However, the synthetic complexity of these nano materials and structures could very possibly bring significant challenges in actual large-scale application.…”
Section: Introductionmentioning
confidence: 99%